PTH-013 Routine Coagulation Profile Prior To Ercp – An Unnecessary Investigation?. (9th June 2014) - Onos, L; Wyman, A
Abstract : Introduction: From the first reported endoscopic retrograde cholangiopancreatography (ERCP) in 1968 to the invention of endoscopic sphincterectomy in 1974, ERCP has evolved to an almost entirely therapeutic procedure. It is appreciated that approximately 54, 000 patients undergo ERCP each year. 1 The 2008 British guidelines include routine pre-procedural coagulation screen within 3 days prior to ERCP. 2 However, the American Society for Gastrointestinal Endoscopy guidelines state that the prothrombin time, International Normalised Ratio (INR), and activated partial thromboplastin time in patients without clinical evidence of bleeding disorder or coagulopathy do not predict or correlate with either intraoperative or postoperative haemorrhage. 3 Methods: A 12-month retrospective study of 440 patients undergoing ERCP in a single UK tertiary institution was undertaken. The correlation between the presence of a biochemical cholestatic picture and the INR was assessed. Results: The blood results of 440 patients were reviewed using the ICE (Integrated Clinical System). The median age was 67-years. Of the 440 patients, 310 had deranged LFTs, 86 had a normal liver profile, and 44 had no LFTs taken prior to ERCP. Of those with deranged LFTs, 2% had only a raised bilirubin, less than 6% had either only raised transaminases or both raised transaminases and bilirubin, 12% had only both raised alkaline phosphatase (ALP) and bilirubin, 15% had both raised ALP and transaminases, 22% had only raised ALP, and 43% had a trio of raised bilirubin, ALP, and transaminases. Only 11 patients had no coagulation profile taken before the procedure. Out of the remaining 429 patients, 15 were on warfarin, 2 had haemophilia, 1 was thrombocytopenic, and 1 had von Willebrand's disease. However, out of 440 patients only 2 had an INR greater than 1.5, 1 of them being on warfarin. Conclusion: These results suggest that routine measurement of coagulation profile is unnecessary. This would reduce time delays, decrease costs and avoid further tests in patients. We suggest that the current pre-ERCP investigation guidelines be reviewed. 4 References: The future of service and training in ERCP in UK-J. R. B. GREEN and The UK ERCP Stakeholders working party- August 2007-British Society of Gastroenterology J Williams, J Green, I Beckingham, R Parks, D Martin, M Lombard-Guidelines on the management of common bile duct stones- Gut 2008;57:1004–1021. doi:10.1136/gut.2007.121657 Position statement on routine laboratory testing before endoscopic procedures-http://www.asge.org Baillie John, Pier‐Alberto Testoni. Are we meeting the standards set for ERCP? Gut. 2007 June; 56(6):744–746. doi: 10.1136/gut.2006.113456 Disclosure of Interest: None Declared.